Identifying the Legislative Techniques of Criminalization in the Criminal Code 2015 and some Recommendations - Hoang, Vu Dinh (VNU Journal of Science: Legal Studies, 2023)
Criminalization is a part of criminal justice policy and one of the most important and frequently-used legislative methods in criminal law. It creates a legal basis for combating crimes and ensures the effectiveness of the Criminal Code. Identifying the legislative techniques of criminalization in the Criminal Code 2015 is essential to minimize shortcomings in the implementation process of this legislative activity.